(untitled) (International Journal of Contemporary Security Studies, 2023)
The author discusses the importance of criminal justice protection in the Republic of Serbia in reducing the risk of disasters. The main assumption is that criminal law also has an impact on the valid application of disaster risk reduction rules, apropos, their prevention. The analysis begins with a theoretical determination of the character of the criminal response (subsidiarity, general and special prevention), then clarifying the meaning of certain terms that constitute a risk reduction system, that are part of the country’s national security system (disasters, accidents, emergencies, calamities, etc). We will analyze crimes such as Aggravated larceny committed during a fire, flood, earthquake or other calamity, failure to takе part in eliminating a general hazard, and for this area characteristic of crimes against the environment and general safety of people and property. Prescribing these crimes (in addition to the provisions of the Law on disaster risk reduction and emergency management), expands the possibilities of protection against injury or endangerment of goods "affected by disasters". These incriminations further "strengthen" citizens’ obligations as subjects of a disaster risk reduction system. Given the importance of security culture in this area, we will examine the adequacy of existing criminal regulations and consider the possible need to change existing or introduce new incriminations. A review will also be given on the reasons for delegating jurisdiction over these occurrences.